Budesonide for the Induction and Maintenance of Remission in Crohn's Disease: Systematic Review and Meta-Analysis for the Cochrane Collaboration. Issue 4 (24th May 2018) - Kuenzig, M Ellen; Rezaie, Ali; Kaplan, Gilaad G; Otley, Anthony R; Steinhart, A Hillary; Griffiths, Anne Marie; Benchimol, Eric I; Seow, Cynthia H
Abstract: Background: Budesonide is an oral glucocorticoid designed for the treatment of inflammatory bowel disease (IBD) that may reduce systemic adverse events (AEs). This review examined the efficacy and safety of budesonide for the induction and maintenance of clinical remission in Crohn's disease (CD). Methods: MEDLINE, EMBASE, other electronic databases, reference lists and conference proceedings were searched to November 2017 to identify randomized controlled trials of budesonide. Outcomes were the induction and maintenance of remission at eight weeks and one year, respectively, as well as corticosteroid-related AEs and abnormal adrenocorticotropic hormone (ACTH) tests. Pooled relative risks (RRs) and 95% confidence intervals (CIs) were estimated using random effects models. Results: Thirteen induction and 10 maintenance trials were included. Budesonide 9 mg/day was more effective than placebo (RR 1.93; 95% CI, 1.37–2.73; GRADE: moderate) but less effective than conventional steroids (RR 0.85; 95% CI, 0.75–0.97; GRADE: moderate) to induce remission. Corticosteroid-related AEs occurred less often with induction doses of budesonide than steroids (RR 0.64; 95% CI, 0.54–0.76; GRADE: moderate); budesonide did not increase AEs relative to placebo (RR 0.97; 95% CI, 0.76–1.23; GRADE: moderate). Budesonide 6 mg/day was not different from placebo for maintaining remission (RR 1.13; 95% CI, 0.94–1.35; GRADE: moderate). Both induction (GRADE: low for 3 mg/day, moderate for 9 mg/day) and maintenance budesonide treatment (GRADE: very low for 3 mg/day, low for 6 mg/day) increased the risk of an abnormal ACTH test compared with placebo, but less than conventional steroids (GRADE: very low for both induction and maintenance). Conclusion: For induction of clinical remission, budesonide was more effective than placebo, but less effective than conventional steroids. Budesonide was not effective for the maintenance of remission. Budesonide was safer than conventional steroids, but the long-term effects on the adrenal axis and bone health remain unknown.